2014
DOI: 10.1128/iai.00052-14
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a Single CD4 T Cell Peptide Epitope from a Salmonella Type III-Secreted Effector Protein Provides Protection against Lethal Infection

Abstract: Salmonella infections affect millions worldwide and remain a significant cause of morbidity and mortality. It is known from mouse studies that CD4 T cells are essential mediators of immunity against Salmonella infection, yet it is not clear whether targeting CD4 T cell responses directly with peptide vaccines against Salmonella can be effective in combating infection. Additionally, it is not known whether T cell responses elicited against Salmonella secreted effector proteins can provide protective immunity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…The importance of CD4 T cells in controlling chronic virus infection has made them a focus in the context of vaccine development (43,44). To assess whether these cells have the capacity to provide protection against CMV in a vaccine setting, immunocompetent mice received a single vaccination with m53 and m78 peptides in CFA, followed by MCMV challenge and assessment of viral replication 4 days later.…”
Section: Fig 2 Phenotypic Analysis Of M78-specific Cd4 T Cells After mentioning
confidence: 99%
“…The importance of CD4 T cells in controlling chronic virus infection has made them a focus in the context of vaccine development (43,44). To assess whether these cells have the capacity to provide protection against CMV in a vaccine setting, immunocompetent mice received a single vaccination with m53 and m78 peptides in CFA, followed by MCMV challenge and assessment of viral replication 4 days later.…”
Section: Fig 2 Phenotypic Analysis Of M78-specific Cd4 T Cells After mentioning
confidence: 99%
“…However, due to a rise in antibiotic resistance of NTS (Feasey et al, 2012;Lunguya et al, 2013), the emergence of the highly antibiotic resistant and virulent ST313 strain in sub-Saharan Africa (Kingsley et al, 2009;Okoro et al, 2012), and the increasing severity of NTS-mediated disease in developed countries, a pressing need exists for the development of an effective vaccine to prevent NTS infection. Vaccine strategies for NTS have included: 1) liveattenuation of housekeeping genes or genes that are important for essential biosynthetic processes such as aro (Hormaeche et al, 1990(Hormaeche et al, , 1991, dam (Heithoff et al, 2001), crp/ cdt (Zhang et al, 1997b(Zhang et al, , 1999, relA/ spoT (Na et al, 2006), or guaA/ clpP/ fliD (Tennant et al, 2011); 2) conjugate vaccines consisting of conjugation of the lipopolysaccharide (LPS)-derived serovar-specific O-polysaccharide to protein (Jazani et al, 2005;Simon et al, 2011bSimon et al, , 2013Svenson et al, 1979;Watson et al, 1992); and 3) subunit vaccines utilizing peptides from the type 3 secretion system (T3SS) (Kurtz et al, 2014), fimbriae (Pang et al, 2013), and flagellin (Bobat et al, 2011). Nevertheless, despite years of research no licensed human NTS vaccines currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that IL-17 and its associated cytokines (IL-21 and IL-22) are induced in the gastrointestinal tract during Salmonella infection (Ramarathinam et al, 1993; Lee et al, 2012; Kurtz et al, 2014; McSorley, 2014). While Th1 cells are critical for activation of infected macrophages to kill Salmonella in the tissues, Th17 cells are likely essential for recruiting neutrophils to the site of intestinal infection to engulf bacteria (Ramarathinam et al, 1993; TĂĽkel et al, 2009; Broz et al, 2012; Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%